THE INFLUENCE OF LEADERSHIP STYLE AND WORK DISCIPLINE ON EMPLOYEE PRODUCTIVITY AT ERAFONE WEST JAKARTA - Andi Sopandi; Kamsidik Kamsidik; Laura Komala; Liawati Liawati; Prihadi Dhasa Eka (Asosiasi Dosen Muda Indonesia, 2025)
The purpose of this study was to determine the effect of leadership style and work discipline on employee productivity at Erafone in West Jakarta. The method used is an associative method with quantitative analysis. The number of samples used was 62 people. The results indicate that leadership style has a significant effect on employee productivity. The regression analysis shows a positive relationship, with a strong correlation coefficient. The coefficient of determination suggests that leadership style contributes significantly to productivity, while the remaining portion is influenced by other factors. The hypothesis test confirms that leadership style has a significant impact on employee productivity. Similarly, work discipline also has a significant effect on employee productivity. The regression analysis demonstrates a strong correlation, with a considerable portion of productivity being explained by work discipline. The hypothesis test supports the conclusion that work discipline plays a crucial role in enhancing employee productivity. When analyzed simultaneously, leadership style and work discipline together have a significant effect on employee productivity. The regression analysis confirms a very strong relationship, with a high coefficient of determination indicating that these two variables account for a substantial portion of productivity. The hypothesis test further validates that leadership style and work discipline jointly influence employee productivity in a meaningful way.